2017
DOI: 10.3171/2016.10.peds16270
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal management of pediatric congenital transsphenoidal encephaloceles: nuances of a modified reconstruction technique. Technical note and report of 3 cases

Abstract: OBJECTIVE Congenital transsphenoidal encephaloceles are rare malformations, and their surgical treatment remains challenging. This paper reports 3 cases of transsphenoidal encephalocele in 8- to 24-month-old infants, who presented mainly with airway obstruction, respiratory distress, and failure to thrive. METHODS The authors discuss the surgical management of these lesions via a minimally invasive endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Endoscopic repair of the meningocele defect is a minimally invasive procedure and is advised for successful treatment of the lesions. [34][35][36] Keshri et al reported six patients with meningocele who underwent surgery using the transnasal endoscopic approach. 35 Ma et al reported a series of 23 patients who underwent surgery for CSF leak with or without encephalocele, 28 and Marfatia et al reported a series of 19 pediatric patients with meningoencephaloceles who underwent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic repair of the meningocele defect is a minimally invasive procedure and is advised for successful treatment of the lesions. [34][35][36] Keshri et al reported six patients with meningocele who underwent surgery using the transnasal endoscopic approach. 35 Ma et al reported a series of 23 patients who underwent surgery for CSF leak with or without encephalocele, 28 and Marfatia et al reported a series of 19 pediatric patients with meningoencephaloceles who underwent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of transpalatal approach was corroborated by the literature that shows high rate of morbidity, mortality, and cerebrospinal fluid fistula in patients operated by cranial and endoscopic access [1,4,[12][13][14].…”
Section: Multidisciplinary Team Simulationmentioning
confidence: 99%
“…A basal encephalocele is defined as a neural element herniation, including the pituitary gland or optic chiasm, through an anatomical defect in the base of the skull [1][2][3][4]. They represent 1.5-5% of all cephaloceles, and the transsphenoidal encephalocele is the rarest form [2,5,6], with an incidence estimate of 1 in 700,000 live births [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations